Tinjauan Kekudusan Pelayanan dari Pelayanan Sakramen yang Berdosa menurut Santo Agustinus dari Hippo - Valentinus Febianto Bayu Kurniawan (Parahyangan Catholic University, 2020)
The sacrament is a sign of God’s presence in the world. Through the sacrament mankind finds salvation. Men received the sacraments with the help of priests. Therefore, there is a demand for holiness for the priests. The question is, if as a sacrament minister, a priest does not show holiness, can the sacrament still bring salvation? To answer this question, this paper uses the idea of Saint Augustine of Hippo. Saint Augustine insists that the sacrament can still save because Christ works in it. In addition, there is a de- mand for priests to always practice self-sanctification.